Integration of Liquid Organic Fertilizer Fermentor with Automated Hydroponic Fertilization Based on IoT - Muhammad Fakhrudin Zukhri; Puti Yeni Aisyah; Yudi Wirawan; Tia Yohana Nainggolan; Firda Anandhita; Muhammad Ivan Hermawan (JAREE (Journal on Advanced Research in Electrical Engineering), 2025)
As urbanization continues to accelerate, particularly in cities like Surabaya, the availability of agricultural land has been steadily decreasing, making food security a growing concern. In response to these challenges, urban farming, particularly through hydroponic systems, has emerged as a promising solution to ensure sustainable food production in limited spaces. However, issues such as the high cost and limited availability of high-quality fertilizers, as well as the difficulty in maintaining a consistent farming schedule, have posed significant barriers. This study aims to address these challenges by integrating IoT-based systems for temperature and pH monitoring, aiming to enhance farming efficiency. The validation results for both the DS18B20 Temperature Sensor and the pH Sensor 4502-C demonstrate their high accuracy and reliability for environmental monitoring. The DS18B20 sensor showed minimal error, with 0.89% for increasing temperatures and 1.34% for decreasing temperatures, achieving 99.11% and 98.66% accuracy, respectively. These results confirm the sensor’s effectiveness in real-time temperature control applications, such as those used in hydroponics and fermentation systems. Similarly, the pH Sensor 4502-C exhibited remarkable performance, with 99% accuracy in the acidic buffer, 98.99% in the neutral buffer, and 99% in the basic buffer. The error rates were extremely low, at 0.002% for acidic and basic buffers, and 0.01% for the neutral buffer, reinforcing the sensor’s reliability for pH monitoring in controlled environments.